Sustainability of Sharia Fintech: The Role of Perceived Benefit And Perceived Risk - Supriyanto, Agus; Fagustina, Anis (MALIA: Journal of Islamic Banking and Finance, 2024)
This study aims to examine the influence of Perceived Benefit and Perceived Risk on Intention to use Sharia Fintech and its impact on the sustainability of Sharia Fintech. The research sample consisted of 137 respondents selected using purposive sampling method. The results of the study indicate that perceptions of benefits and risks have a significant influence on users' intention to adopt Sharia Fintech. Users' intention, as a direct result of perceptions of benefits and risks, plays a crucial role in maintaining the sustainability of the Sharia Fintech industry. Recommendations for future research include the development of strategies focused on enhancing perceptions of benefits and reducing perceptions of risks associated with the use of Sharia Fintech. Furthermore, further research is needed to understand other factors that may influence users' intentions and the sustainability of the Sharia Fintech industry, in order to formulate more comprehensive and sustainable development strategies.